Effect of passive and forced aeration on composting of market solid waste - Atauzzaman, M.; H. Bari, Q. (International Journal of Engineering and Technology, 2020)
This study aimed to determine the effect of passive and forced aeration on composting of market wastes. Suitable vegetable waste, waste paper and sawdust as bulking agent were mixed with the proportion 75:10:15. Temperature inside composting reactors was measured daily time to time. Total sample and volatile solids were determined before and after composting of waste mixture with both passive and forced aeration. Temperature increased to maximum 52 ºC for passive aeration and 54 ºC for forced aeration. The percentage reduction in total sample was found to be greater for forced aeration than passive aeration. The volatile solids decreased with time at the end of both processes. The extent of volatile solids degradation of waste mixture with time was determined through forced aeration for a series of composting process. Total sample and volatile solids were determined at 2, 3 or 4 days interval. The percentage reductions in total    sample and volatile solids were found to be varied from 3 to 68 % and 4 to 55% respectively. The percentage reduction in volatile solids increased with time. There is a possibility of recycling the waste mixture in the form of composting.